Konsep Pariwisata Hijau Bagi Pemulihan Model Pariwisata Indonesia Pasca Pandemi Covid-19 - Ika Sri Hastuti; Melaty Anggraini; Imam Budiman (Peneliti.net, 2023)
This study examines Indonesia's tourism strategy after the Covid 19 Pandemic, where the Indonesian tourism sector has experienced a decrease in economic income due to the Covid 19 pandemic. It requires closing all tourist destinations to prevent the spread of the Covid 19 virus. After the pandemic or entering the